Biocatalytic self-propelled submarine-like metal-organic framework microparticles with pH-triggered buoyancy control for directional vertical motion. (September 2019) - Guo, Ziyi; Wang, Tao; Rawal, Aditya; Hou, Jingwei; Cao, Zhenbang; Zhang, He; Xu, Jiangtao; Gu, Zi; Chen, Vicki; Liang, Kang
Graphical abstract: Self-propelled submarine-like microparticles that can exploit buoyancy force for directional vertical motion is reported. A slight shift in pH can cause the generated gas bubbles to be reversibly retained/expelled from the micromotor particles, leading to the buoyancy-directed vertical motion with speed regulation. This study will open up new avenues for designing directional propulsion mechanisms for chemical motors and robotics, showing potential as smart cargo transport microsystems that are sensitive to their environment. Abstract: Self-propelled chemical motors have found vast promise for applications from nanomedicine to environmental remediation. However, strategies for controlling their directional motion on demand still represents one of the major challenges for the development of smart motor systems to be realized in real-world applications. Here, we report for the first time the design of a novel submarine-like micromotor that is capable of directional vertical motion on centimeter scale by pH-regulated buoyancy control. With the aid of a pH-responsive, hydrophilic/hydrophobic phase-shifting polymer, gas bubbles produced by the biocatalytic metal–organic framework micromotors can be reversibly retained/expelled from the micromotors, leading to the buoyancy-controlled ascending or descending vertical motion. Importantly, anti-cancer drug-loaded micromotors showed directional cytotoxicity to three-dimensional cell cultures, depending on the pH of the cellular environment. We expect this study will open up new avenues for designing directional propulsion mechanisms for chemical motors, showing potential as autonomous robotics for in vivo delivery in complex biological environments.